2012
DOI: 10.1149/2.009204jss
|View full text |Cite
|
Sign up to set email alerts
|

Process Study and Characterization of VO2Thin Films Synthesized by ALD Using TEMAV and O3Precursors

Abstract: Vanadium oxide (VO2) thin films were prepared by atomic layer deposition using TEMAV (tetrakis[ethylmethylamido]vanadium) precursor and ozone as the reactant gas. Study on the precursor as well as oxidizer doses and temperature dependence showed none of them exhibited the characteristics of ideal ALD. The VO2 phase formation pathways, its process window, and surface roughness are found to be sensitive to the anneal conditions applied and the substrate used. The VO2 morphology on Al2O3 was found to be island-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
62
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 42 publications
2
62
0
Order By: Relevance
“…Rampelberg et al found that the V(NEtMe) 4 /ozone process deposited amorphous VO 2 thin films that crystallized into the monoclinic VO 2 when annealed at 450°C under an inert atmosphere . In contrast, Premkumar et al obtained amorphous V 2 O 5 with liquid injected V(NEtMe) 4 and ozone, and the films remained amorphous even after annealing at 425°C in N 2 . When annealed in the presence of oxygen, the films crystallized but the resulting phases were strongly dependent on the partial pressure of the oxygen.…”
Section: Ald Of Groups 4 and 5 Oxide Thin Filmsmentioning
confidence: 99%
“…Rampelberg et al found that the V(NEtMe) 4 /ozone process deposited amorphous VO 2 thin films that crystallized into the monoclinic VO 2 when annealed at 450°C under an inert atmosphere . In contrast, Premkumar et al obtained amorphous V 2 O 5 with liquid injected V(NEtMe) 4 and ozone, and the films remained amorphous even after annealing at 425°C in N 2 . When annealed in the presence of oxygen, the films crystallized but the resulting phases were strongly dependent on the partial pressure of the oxygen.…”
Section: Ald Of Groups 4 and 5 Oxide Thin Filmsmentioning
confidence: 99%
“…In addition, the occurrence of multiple VO 2 polymorphs further emphasises the challenge to synthesize stoichiometric and phase pure monoclinic VO 2 . Various methods for the synthesis of VO 2 have been reported including chemical vapour deposition, 5,12 atomic layer deposition, 13,14 pulsed laser deposition 5,15 and sputtering. 5,16,17 Wet chemical synthesis routes are widely considered as valuable alternatives for the vacuum based techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, various preparation approaches have been developed for VO x thin films, such as sol-gel, 12 spray pyrolysis, 13 electrodeposition, 14 evaporation, 15 magnetron sputtering, 16 pulsed laser deposition, 17 chemical vapor deposition, 18 and atomic layer deposition (ALD). 6,8,[19][20][21][22][23][24][25][26][27][28][29][30][31][32] Among these approaches, ALD is of particular interest for preparing thin films. ALD employs alternate saturated self-limiting surface chemistry reactions, and allows one to deposit thin films in a well-controlled layer-by-layer fashion.…”
mentioning
confidence: 99%
“…A similar precursor, vanadium n-propoxide, could also be used along with acetic acid to produce ALD V 2 4 ] was described with water or ozone for depositing VO x thin films. [28][29][30] In this case, since metalnitrogen bonds are generally weaker than metal-oxygen bonds in transition metal organic compounds, V(NEtMe) 4 should be more reactive toward forming oxides in ALD. Also, V is in nominal 14 valence state in V(NEtMe) 4 , and it should be therefore more favorable for depositing stoichiometric VO 2 thin films.…”
mentioning
confidence: 99%